Expression patterns of β-defensin and cathelicidin genes in parenchyma of bovine mammary gland infected with coagulase-positive or coagulase-negative Staphylococci - Kościuczuk, Ewa M (BioMed Central, 2014)
BACKGROUND: Mastitis is still considered to be the most economically important infectious disease in dairy cattle breeding. The immune response in mammary gland tissues could help in developing support strategies to combat this disease. The role of neutrophils and macrophages in the innate response of mammary gland is well known. However, the immune response in mammary gland tissues, including levels of antimicrobial peptide transcripts, has not been well recognized. Moreover, most studies are conducted in vitro, on cell cultures, or on artificially infected animals, with analysis being done within a several dozen hours after infection. The aim of the study was to examine the in vivo transcript levels of beta-defensin and cathelicidins genes in cow mammary gland secretory tissue (parenchyma) with the chronic, recurrent and incurable mammary gland inflammation induced by coagulase-positive or coagulase-negative Staphyloccoci vs. bacteria-free tissue. RESULTS: The mRNA of DEFB1, BNBD4, BNBD5, BNBD10 and LAP genes, but not of TAP gene, were detected in all investigated samples regardless of the animals’ age and microbiological status of the mammary gland, but at different levels. The expression of most of the beta-defensin genes was shown to be much higher in tissues derived from udders infected with bacteria (CoPS or CoNS) than from bacteria-free udders, regardless of parity. Cathelicidins (CATH4, CATH5 and CATH6) showed expression patterns contrasting those of β-defensins, with the highest expression in tissues derived from bacteria-free udders. CONCLUSION: Increased expression of genes encoding β-defensins in the infected udder confirms their crucial role in the defense of the cow mammary gland against mastitis. On the other hand, the elevated cathelicidin transcripts in non-infected tissues indicate their role in the maintenance of healthy mammary tissues. The expression levels of investigated genes are likely to depend on the duration of the infection and type of bacteria. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12917-014-0246-z) contains supplementary material, which is available to authorized users.